EFEKTIFITAS METODE PELATIHAN TERHADAP PENINGKATAN KEMAMPUAN KADER DALAM PENCEGAHAN DAN PENANGANAN STUNTING : LITERATURE REVIEW - Simanjuntak, Susi Roida (JURNAL KEPERAWATAN, 2025)
Background: Stunting remains a global issue, including in Indonesia. Various efforts have been made to prevent and reduce the incidence of stunting. One of these efforts is enhancing the capacity of Posyandu cadres in stunting prevention and management. Objective: This literature review aims to determine the impact of training on improving cadres' abilities in stunting prevention and management. Methods: Article searches were conducted using the ScienceDirect, Medline/PubMed, and Google Scholar databases. Articles were selected based on inclusion criteria, namely, limited to the last five years (2019-2024), primary research articles, and full-text availability. Results: Eight articles met the criteria for this review study. All research articles originated from Indonesia. The training methods used in the reviewed studies varied. Conclusion: This review identifies a correlation between training and the improvement of cadres' knowledge and skills in stunting prevention and management. Keywords: Cadre; Training; Stunting